UNJUK KERJA ALAT PENGERING GULA SEMUT DUA BELAS SUSUN MENGGUNAKAN BAHAN BAKAR LPG - Johanes, Susanto; G., Sukartono,; S., Soeadgihardo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Modified dryer is used as an alternative methodfor drying the production of coconut sugars (gula semut / gula merah) or coconutcrystal sugars for farmers or micro entrepreneurs, especially when production is increased or in the rainyseason. This study aims to determine the performance of drier gula semut own design, with LPG fuel. Construction drier consists of a framework to support stainless steel pans as the container of sugars, measuring 78 cm x 74 cm x 4 cm, which is composed of twelve level, with a gap distance of 5 cm. The pans arranged vertically, so that the bottom of the pan gets hot either by radiation, conduction, and convection by the flow of hot air that is exhaled by the blower, while the pans that is above it also will get heat by conduction and convection by hot air which flows through it. The tests of dryers are conducted in two methods: with load and without load. The weather conditions are dry bulb temperature of 30°C and 27°C wet bulb. In the no-loaded testing, to achieve a working temperature of the drying chamber at 60 °C, it takes approximately 40 minutes. While testing with load is drying 8 kg / pan and 10 kg / pan sugars. On this burden, to reduce the water content of about 6% to between 2-3%, required 5.5-7 hoursdrying time, and required the consumption of fuel (LPG) between 1.15 to 1.35 kg. The rate of the average water content decreasedis 0.66% per hour, and the total efficiency of the dryer (ηT) is 23%.